Study of Tribal and Alaska Native Juvenile Justice Systems in The United States, 1990 ([Verlag nicht ermittelbar], 1992)
This data collection focuses on juvenile justice systems administered by federally recognized Indian tribes throughout the United States. Responses were received from 93 tribes who indicated that they administered some form of juvenile justice system and from 57 tribes who indicated that they did not. Variables in the data collection include number of Indian juveniles aged 10-17 in the jurisdiction, types of cases that the juvenile justice system exercised jurisdiction over, type of court (tribal, state, federal), annual budget and sources of funds for the court, number of court personnel, types of legal statutes covering court activities, kinds of diversionary options available to the court, and the circumstances under which juveniles were held with adults. A separate file on juvenile offense rates according to tribe is provided.